Attention across modalities as a longitudinal predictor of early outcomes: The case of fragile X syndrome - Scerif, G; Longhi, E; Cole, V; Karmiloff-Smith, A; Cornish, K (2012)
Background: Fragile X syndrome (FXS) is an early diagnosed monogenic disorder, associated with a striking pattern of cognitive/attentional difficulties and a high risk of poor behavioural outcomes. FXS therefore represents an ideal model disorder to study prospectively the impact of early attention deficits on behaviour. Methods: Thirty-seven boys with FXS aged 4-10 years and 74 typically developing (TD) boys took part. Study 1 was designed to assess visual and auditory attention at two time-points, 1 year apart. Study 2 investigated attention to multimodal information. Both tested attention markers as longitudinal predictors of risk for poor behaviour in FXS. Results: Children with FXS attended less well than mental-age matched TD boys and experienced greater difficulties with auditory compared to visual stimuli. In addition, unlike TD children, they did not benefit from multimodal information. Attention markers were significant predictors of later behavioural difficulties in boys with FXS. Conclusions: Findings demonstrate, for the first time, greater difficulties with auditory attention and atypical processing of multimodal information, in addition to pervasive global attentional difficulties in boys with FXS. Attention predicted outcomes longitudinally, underscoring the need to dissect what drives differing developmental trajectories for individual children within a seemingly homogeneous group. © 2011 The Authors. Journal of Child Psychology and Psychiatry.